Field notes contributed by Beth Proescholdt, Liscomb, Iowa, spring 1984 - Proescholdt, Bethet al (1984)
Field notes were contributed by Beth Proescholdt, Liscomb, Iowa, spring 1984. Other observers were Mark Proescholdt, Phyllis Harris, and Ramona R. Sommerlot. Documented sightings were of a Northern Goshawk, Peregrine Falcon, Pine Warbler, Red-necked Grebe, and Barrow's Goldeneye. Also included was a letter to Thomas H. Kent regarding absence of birds, particularly warblers, May 29, 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed